Development and calidation of the psychometric properties underpinning the Kwaito Music Attitude and Perception Scale (KMP) - Williams, Akhona (Rhodes University, Faculty of Humanities, Department of Psychology, 2021)
Music holds a privileged position in enhancing therapeutic well-being, supporting life skills development in youth and adolescents, and shaping cultural identities. As such, music has been closely related to youth culture, especially as it pertains to youth rehabilitation and identity formation. Studies (e.g., Duffy and Fuller, 2000; Miranda et al, 2013; Strayhorn, 2011; Tomasello, 2016) highlight the value of utilising music in youth rehabilitation, and acknowledge the intrinsic value of music to facilitate psychological and social change for individuals who would not otherwise benefit from psycho-education, or other didactic modes of youth rehabilitation. That said, Tyson (2005) developed the RAP music scale to psychometrically validate the underlying constructs of youth' attitudes and perception of rap music in the United States of America, in order to use the instrument for music-based youth rehabilitation programs. The development of the RAP music scale informed the creation and validation of the Kwaito-music Attitude and Perception (KMP) Scale, the subject of my Masters thesis. Following suggestions from Morrison (2014), my study sought to psychometrically validate the properties of the Kwaito-music Attitude and Perception (KMP) Scale. The KMP was found to be a reliable measure of kwaito music attitudes and perception amongst a sample of South African youth who listen to this genre of music. The internal consistency of the questionnaire revealed a Cronbach's Î± (Alpha) value of 0.820. Limitations of the project including reduced factor extraction and sample size constrains are discussed. It is envisioned that results from this study will find resonance with youth-community programs, and rehabilitation projects utilising music as a medium of healing amongst South African youth.
Keywords: Kwaito-music Attitude and Perception; Chronbach's alpha; Kwaito (Music); Psychotherapy and music -- South Africa; Problem youth -- Rehabilitation -- South Africa; Attitude (Psychology) -- Testing -- South Africa; Perception -- Testing -- South Africa